Attentional signals projecting centrifugally to the avian retina: A dual contribution to visual search. (June 2022) - Uchiyama, Hiroyuki; Ohno, Hiroshi; Kawasaki, Takuto; Owatari, Yuhki; Narimatsu, Takahiro; Miyanagi, Yusaku; Maeda, Taiga
Abstract: Among vertebrates, birds have a particularly well-developed retinopetal system, i.e., the centrifugal system projecting from the brain to the retina. Primary, secondary and tertiary neurons of the retinopetal system connect serially in a one-to-one-to-one fashion, thereby assembling several thousand retinopetal modules projecting in parallel to the retina. The signal conveyed by the retinopetal system enhances the visual responses of retinal ganglion cells (RGCs), and each retinopetal module may facilitate the RGCs in a topographically restricted area. We investigated how the retinopetal signal contributes to visual search by first training Japanese quail to search and peck a target stimulus presented on one of three touch-sensor monitors around the bird and then examining the effect of retinopetal signal blockage on the task. Our results indicate that the retinopetal signal improves both stimulus detectability and target discriminability. Thus, this study confirms that the avian retinopetal system functions specifically in attentional facilitation of the retina; this new finding suggests that this system benefits early detection and late selection phases of visual search. The fast and precise target detection facilitated by the retinopetal signal may be transformed into quick and correct orienting to the target through visuomotor transformation mechanisms implemented in the optic tectum.